IstikhdÄm Kahoot Kawasilah Taâ€™lÄ«miyah Tafaâ€™uliyah bi Al-Arabiyyah - Erma Febriani (Arabic Education Program IAIN Pekalongan, 2019)
This study aims to determine students' perceptions of the use kahoot as an interactive learning media in Arabic in increasing motivation to learn Arabic. The approach used is descriptive quantitative. The subject of this study was a total of 40 students. Data collection techniques are carried out by observation, questionnaire, interview and documentation. Data analysis techniques were carried out using statistical product and service solution (SPSS) technique version 20.00. The use of kahoot as an interactive learning media in Arabic is the focus of the study. The findings of this study indicate that learning using kahoot media is very interesting with a percentage of 82.50%, students get positive things with a percentage of 62.50% strongly agree and 37.50% agree, kahoot media fosters student motivation in learning Arabic with a percentage of 52, 50% agree, 40.00% strongly agree, kahoot makes learning more interactive with a percentage of 40% female students agree, 40% of children strongly agree. Thus it can be concluded that the use of kahoot can foster student motivation and make Arabic learning more interactive.